Protagonist of breastfeeding or an instrument of child health policy?: the enunciation of women in official promotional and guidance materials to breastfeeding - Kalil, Irene Rocha; Aguiar, Adriana Cavalcanti de (Saúde e Sociedade, 2016)
This article examines recent promotion and guid ance materials to breastfeeding produced by the Brazilian Ministry of Health, identifying similari ties and differences between the discourses aimed at pregnant and lactating women, and those directed to health professionals in relation to the proposed meanings about women. Based on the theory of enunciation, we identified that, while the self or subject of enunciation is still present in the ana lyzed discourse (identified as Brazilian Ministry of Health), significant distinctions persist in the ap proach of the women's role. In manuals for health professionals, in which the woman is the subject of whom it talks about, she is commonly represented as an individual with subjectivity who is the protago nist of the process. On the other hand, in materials aimed at women, we observed that, in general, they are treated in an objectified way, revealed through a normative and imperative language, which quali fies them as an instrument of the official policy for child's health. We argue that understanding how the object spoken is created by/in these discourses, unveiling how positions and power relations are constructed in them, enables us to discuss this com munication that generally has neglected the experi ences and expectations of mothers in breastfeeding.